Power grid complexity - Mei, Shengwei 1964- (Springer Tsinghua University Press, 2011)
Power Grid Complexity introduces the complex system theory known as self-organized criticality (SOC) theory and complex network theory, and their applications to power systems. It studies the network characteristics of power systems, such as their small-world properties, structural vulnerability, decomposition and coordination strategies, and simplification and equivalence methods. The book also establishes four blackout models based on SOC theory through which the SOC of power systems is studied at both the macroscopic and microscopic levels.  Additionally, applications of complex system theory in power system planning and emergency management platforms are also discussed in depth. This book can serve as a useful reference for engineers and researchers working with power systems. Shengwei Mei is a Professor at the Department of Electrical Engineering at Tsinghua University, China. Xuemin Zhang is a Lecturer at the Department of Electrical Engineering at Tsinghua University, China. Ming Cao is an Assistant Professor at the Faculty of Mathematics and Natural Sciences at the University of Groningen, the Netherlands.